Using Plotagon Application to Enhance English Presentation Skill of SMP Telkom Makassar Students - Fitriana, Fitriana; Korompot, Chairil Anwar; Aeni, Nur (Journal of Excellence in English Language Education, 2024)
This research aimed to determine whether the use of the Plotagon Application is effective in enhancing students’ English Presentation skills. The researcher used a pre-experimental as a research design. This research focuses on a single group pre-test and post-test which asks students to present in front of the class on the topic of daily activities. This research was conducted at SMP Telkom Makassar in the eighth grade with a total population of 230 students. The sample was class VIII B with a total of 30 students selected using a random sampling technique. The findings from this study showed that the mean score of pre-tests was 68.11 and post-test was 84.55, this means that the score was increased after the sample received treatment and based on the paired sample on sig. value (2-tailed) was 0.00 < 0.05. It can be concluded that the use of the Plotagon application is effective in enhancing students' English presentation skills.